If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+x+x+6x=27
We simplify the equation to the form, which is simple to understand
x+x+x+6x=27
We move all terms containing x to the left and all other terms to the right.
+1x+1x+1x+6x=+27
We simplify left and right side of the equation.
+9x=+27
We divide both sides of the equation by 9 to get x.
x=3
| 2.5y+4=2y-1 | | 9(y+10)+y=2(y+3)-5 | | .4x+.8= | | -7z+3z=8z-3-z | | 2-8/2(x-1)^2+15 | | .75y-7=-1 | | 31/3/55/12 | | 4x-9=5x-4 | | 3-3/2=7*3/2-9 | | (6x^3-5x^2-4x+3)/(x-1) | | (5-y)(2y-7)=0 | | 2*15/4-6+15/4=6*15/4+9 | | 8(y+2)+y=2(y+2)+7 | | 23x-16=205 | | .67x=14 | | .75y-.5=7 | | (6x^3-5x^2-4x+3)/x-1 | | 9-2x-5-4x=7 | | 2(4x+3)=8x+6 | | 8y-1=4y+9 | | 0.25x+27=41 | | -0.572x=-8 | | -4(n+5)=8-3n | | 31n(2x)=15 | | (((6x-7)/(6x+6))+1)/(((6x-7)/(6x+6))-1) | | y=10/7*1-10 | | 6=5+5e^6x | | 44=5x-8-x | | 7(x-3)=8x+2 | | 5/12/10/36+1/2= | | 16b^7p^8-36b^5p^6+36b^3p^4/4b^3p | | -5*16+6/2-16= |